2015
DOI: 10.1016/j.ejphar.2015.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repeated quetiapine treatment on conditioned avoidance responding in rats

Abstract: The present study characterized the behavioral mechanisms of avoidance-disruptive effect of quetiapine in the conditioned avoidance response test under two behavioral testing (2 warning signals vs. 1 warning signal) and two drug administration conditions (subcutaneous vs. intravenous). In Experiments 1 and 2, well-trained adult male Sprague-Dawley rats were tested under the subcutaneous (s.c.) quetiapine treatment (5.0, 15.0, 25.0, 50.0 mg/kg) for 7 days in a novel procedure consisting of two conditioned stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…It is suggested that simultaneous blocking of dopamine D 2 and 5-HT 2A receptors improves the efficacy of antipsychotic drugs in patients with schizophrenia and reduces the risk of extrapyramidal symptoms (EPS) ( Andree et al, 1997 ; Kusumi et al, 2015 ). The conditioned avoidance response study is a well-established preclinical antipsychotic animal model ( Wadenberg et al, 2000 ; Gao et al, 2015 ). Antipsychotic drugs can selectively suppress the conditioned avoidance response of rats.…”
Section: Discussionmentioning
confidence: 99%
“…It is suggested that simultaneous blocking of dopamine D 2 and 5-HT 2A receptors improves the efficacy of antipsychotic drugs in patients with schizophrenia and reduces the risk of extrapyramidal symptoms (EPS) ( Andree et al, 1997 ; Kusumi et al, 2015 ). The conditioned avoidance response study is a well-established preclinical antipsychotic animal model ( Wadenberg et al, 2000 ; Gao et al, 2015 ). Antipsychotic drugs can selectively suppress the conditioned avoidance response of rats.…”
Section: Discussionmentioning
confidence: 99%
“…Dosing of animals orally was done by the method of Kuentz, 2012 [48][49][50][51][52], and was followed for all the intranasal drug delivery of quetiapine. The dose of 20 mg/kg was used for the study [51,53].…”
Section: In-vivo Studymentioning
confidence: 99%